Choroidal metastases: Origin, features, and therapy - Sruthi Arepalli; Swathi Kaliki; Carol L Shields (Indian Journal of Ophthalmology, 2015)
The choroid is the most common ocular site for metastatic disease, owing to abundant vascular supply. The primary cancers that most commonly lead to choroidal metastases include breast cancer (40-47%) and lung cancer (21-29%). Bilateral, multifocal metastases are most often secondary to breast cancer, whereas unilateral, unifocal metastasis are more commonly found with lung cancer. The treatment of choroidal metastasis depends on the systemic status of the patient and number, location, and laterality of the choroidal tumors. Treatment options include observation in patients with poor systemic status or those with resolved or asymptomatic disease; systemic chemotherapy, immunotherapy, hormone therapy, or whole eye radiotherapy if the metastases are active, multifocal and bilateral; plaque radiotherapy, transpupillary radiotherapy, or photodynamic therapy for active, solitary metastasis; and enucleation for those with blind painful eye. A database search was performed on PubMed, using the terms "choroidal metastasis," or "choroidal metastases," in combination with terms such as "treatment," "features," or "diagnosis." Relevant articles were extracted and reviewed.